Detection of Intestinal Dysbiosis in Post-COVID-19 Patients One to Eight Months after Acute Disease Resolution - Ferreira-Junior, Alexandre Soares [UNESP]; Borgonovi, Tais Fernanda [UNESP]; Salis, Larissa Vedovato Vilela de [UNESP]; Leite, Aline Zazeri [UNESP]; Dantas, Amanda Soares; Salis, Guilherme Vedovato Vilela de; Cruz, Giuliano Netto Flores; Oliveira, Luiz Felipe Valter de; Gomes, Eleni [UNESP]; Penna, Ana Lucia Barretto [UNESP]; De Oliveira, Gislane Lelis Vilela [UNESP] (Mdpi, 2022)
The intestinal microbiota plays an important role in the immune response against viral infections, modulating both innate and adaptive immune responses. The cytokine storm is associated with COVID-19 severity, and the patient's immune status is influenced by the intestinal microbiota in a gut-lung bidirectional interaction. In this study, we evaluate the intestinal microbiota of Brazilian patients in different post-COVID-19 periods, and correlate this with clinical data and the antibiotic therapy used during the acute phase. DNA extracted from stool samples was sequenced and total anti-SARS-CoV-2 antibodies and C-reactive protein were quantified. Compared with controls, there were significant differences in the microbiota diversity in post-COVID-19 patients, suggesting an intestinal dysbiosis even several months after acute disease resolution. Additionally, we detected some genera possibly associated with the post-COVID-19 dysbiosis, including Desulfovibrio, Haemophillus, Dialister, and Prevotella, in addition to decreased beneficial microbes, associated with antibiotic-induced dysbiosis, such as Bifidobacterium and Akkermansia. Therefore, our hypothesis is that dysbiosis and the indiscriminate use of antibiotics during the pandemic may be associated with post-COVID-19 clinical manifestations. In our study, 39% (n = 58) of patients reported symptoms, including fatigue, dyspnea, myalgia, alopecia, anxiety, memory loss, and depression. These data suggest that microbiota modulation may represent a target for recovery from acute COVID-19 and a therapeutic approach for post-COVID-19 sequelae.
Keywords: Post-COVID-19; Intestinal microbiota; Dysbiosis; Antibiotics; Sequelae